The Relationship between Conceptual Understanding and Students' Academic Achievement in Biochemistry Courses - Fitarahmawati; R. Susanti; Ahmad Naharuddin Ramadhan (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Biochemistry is one of the most challenging subjects for students to master, so a conceptual understanding is necessary to grasp its complex and broad concepts. Concept maps can help understand concepts and can also be used as an assessment tool. This study employed a quantitative correlational analysis to examine the relationship between students' conceptual understanding, as assessed through concept maps, and their academic achievement in Biochemistry. The concept map assessment utilized the University of Waterloo rubric, while the academic achievement assessment used the midterm exam results as a basis. Using the Spearman correlational test, it can be concluded that there was no statistically significant correlation between the concept map and the midterm exam score. The different knowledge content or depths likely caused this result compared to the exam. Differences in learning atmosphere, time allocated, and method of working may also contribute to the insignificant correlation between them. A further study was needed to explore the exact reason for it.